2019
DOI: 10.1073/pnas.1913316116
|View full text |Cite
|
Sign up to set email alerts
|

SERF engages in a fuzzy complex that accelerates primary nucleation of amyloid proteins

Abstract: The assembly of small disordered proteins into highly ordered amyloid fibrils in Alzheimer’s and Parkinson’s patients is closely associated with dementia and neurodegeneration. Understanding the process of amyloid formation is thus crucial in the development of effective treatments for these devastating neurodegenerative diseases. Recently, a tiny, highly conserved and disordered protein called SERF was discovered to modify amyloid formation in Caenorhabditis elegans and humans. Here, we use kinetics measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 48 publications
7
56
2
Order By: Relevance
“…The two main influences are sequence/conformation-dependent (left-hand side) or occur as a result of binding to interaction partners (right-hand side). Ham et al, 2010;Falsone et al, 2012;Meinen et al, 2019). Although the binding site on SERF for all of these amyloidogenic proteins has yet to be identified, αSyn was shown to bind via its C-terminal region (residues 110-140) (Falsone et al, 2012).…”
Section: Flanking Regions That Protect Against Aggregationmentioning
confidence: 99%
“…The two main influences are sequence/conformation-dependent (left-hand side) or occur as a result of binding to interaction partners (right-hand side). Ham et al, 2010;Falsone et al, 2012;Meinen et al, 2019). Although the binding site on SERF for all of these amyloidogenic proteins has yet to be identified, αSyn was shown to bind via its C-terminal region (residues 110-140) (Falsone et al, 2012).…”
Section: Flanking Regions That Protect Against Aggregationmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 5, 2021. ; https://doi.org/10.1101/2021.01.05.423442 doi: bioRxiv preprint extended in nature 92 . For α-Syn, the disruption of intra-molecular electrostatic interactions by the positively charged region of MOAG-4/SERF1 was found to expose an amyloid nucleation site 68,95 .…”
Section: Discussionmentioning
confidence: 99%
“…The nuclei act as seeds from which the fibrils grow and have been shown to propagate a specific fibril structure(Petkova et al , 2005; Qiang et al , 2017). In vitro kinetic assays with SERF and MOAG-4 have shown that these peptides accelerate aggregation by acting on the nucleation phase(Meinen et al , 2019; Falsone et al , 2012; Yoshimura et al , 2017; Merle et al , 2019). Recently, we have shown that SERF2 is equally capable to drive amyloid formation of α-Syn and Aβ in vitro through a conserved, positively charged region(Pras et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the interactions between alpha-synuclein and SERF1A or its yeast ortholog ScSERF have been shown to result in the formation of a fully disordered protein complex, which accelerates the primary nucleation of alpha-synuclein amyloid formation (14,46,47).…”
Section: Discussionmentioning
confidence: 99%